The Re-Emergence of Pediatric Pertussis: Insights from a Regional Romanian Hospital - Ioana Rosca; Alina Turenschi; Alexandru Dinulescu; Victoria Lichii (Antibiotics)
Introduction: Pertussis, a vaccine-preventable disease caused by Bordetella pertussis, is resurging globally due to declining immunization rates. This study explores the clinical and epidemiological features of pediatric pertussis cases in a regional Romanian hospital amid growing vaccine hesitancy. Methods: We conducted a retrospective cohort study on 99 children diagnosed with pertussis and admitted to Ploiești Pediatric Hospital between January 2024 and January 2025. Demographic, clinical, laboratory, and radiological data were analyzed using SPSS 25.0. Results: The median age was 11 months (IQR 4–25), with 12.1% under two months, and ineligible for the first DTaP dose. Notably, 72.7% of children were unvaccinated; 59.4% had missed scheduled doses. None of the mothers received the DTaP vaccination during pregnancy. Most cases (55.6%) had bilaterally accentuated interstitial patterns on chest X-ray, significantly associated with vaccination status (p = 0.019). The leukocyte count was higher in children with alveolar infiltrates (p = 0.028), and as the number of vaccine doses increased, the leukocyte count tended to slightly decrease (p = 0.022, R = −0.229). PCR confirmation was obtained after a mean of 2.2 days, with 12.1% of cases confirmed post-discharge. Azithromycin was used in 74.7% of cases, with good tolerability. Conclusions: Low pediatric and maternal vaccine uptake was a major contributor to pertussis resurgence in this cohort. Radiological severity correlated with vaccination status, suggesting that vaccination may confer protection not only against infection but also against severe pulmonary involvement. These findings support urgent public health efforts to restore vaccine confidence and coverage, particularly among vulnerable infant populations and expectant mothers.